2017
DOI: 10.22159/ijpps.2017v9i3.16584
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Antioxidant Activity of Xanthone-Loaded Making (Hodgsonia Heteroclita) Microemulsions

Abstract: Objective: The aim of this study was to incorporate xanthone into Making (Hodgsonia heteroclita) microemulsions and to evaluate the antioxidant activity of the formulations. Methods:Making oil was obtained from the seed of Hodgsonia heteroclite by a screw press machine. The solubility of xanthone in various oils, surfactants, and co-surfactants was investigated. Stable Making microemulsion and microemulsion-based gel were simultaneously loaded with xanthone. Finally, an in vitro xanthone release study was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Xanthones and their derivatives have broad biological activity, especially in the medical field [16]. Their antioxidant activity is good for antimicrobial agents [17]. Furthermore, Abuzaid et al [18] revealed xanthone's benefit for preventing obesity and metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthones and their derivatives have broad biological activity, especially in the medical field [16]. Their antioxidant activity is good for antimicrobial agents [17]. Furthermore, Abuzaid et al [18] revealed xanthone's benefit for preventing obesity and metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%